An introduction to social psychology - Hewstone, Miles; Stroebe, Wolfgang; Jonas, Klaus (Chichester, West Sussex : BPS Blackwell, 2012)
"The fifth edition of this highly successful text, An Introduction to Social Psychology has been fully revised and updated. Accessibility for students has been improved, including better illustrations, greater use of colour and a more approachable format, as well as a wealth of online resources. Combining its traditional academic rigour with a contemporary level of cohesion, accessibility, pedagogy and instructor support, the fifth edition of An Introduction to Social Psychology provides the definitive treatment of social psychology"--
"The fifth edition of Introduction to Social Psychology provides the definitive treatment of social psychology"--
Machine generated contents note: 1. Introducing Social Psychology 2. Research Methods 3. Social Perception and Attribution 4. Social Cognition 5. The Self 6. Attitudes: Content, Structure and Functions 7. Strategies of Attitude and Behaviour Change 8. Social Influence 9. Aggression 10. Prososcial Behaviour 11. Affiliation, Attraction and Close Relationships 12. The Psychology of Groups: Basic Principles 13. Group Performance and Leadership 14. Prejudice and Intergroup Relations 15. Cultural Social Psychology.
"The British Psychological Society."
Includes bibliographical references (p. [537]-600) and indexes.
Keywords: Social psychology; Social psychology -- Europe; PSYCHOLOGY / Social Psychology